Demographic Transition In Japanese Society (Socio-Cultural Study) - Ngurah Indra Pradhana (Diponegoro University, 2020)
This research is a field research by going directly to the community as informants to obtain data. The data were obtained through distributing questionnaires and interviews with young people in the Kobe District, Japan. These problems are summarized in a study entitled: Demographic Transition in Japanese Society One Socio-Cultural Study. In the data collection stage, a questionnaire method and Interview techniques were used. Meanwhile, the method used to analyze the data was descriptive method. In this study, the results of data analysis were presented using informal methods, namely explaining data by describing all elements descriptively. Factors causing the demographic transition experienced by Japanese society at this time include Japan's involvement in the World War, geographic contours that are prone to disasters, high cost of living, and the presence of sophisticated robots that are the choice of entertainers in Japanese society. From the problems that have occurred, there have been several efforts made by the Japanese Government, including announcing a special allowance program for families who want to give birth to more than three children. A working mother can use quite long leave both before and after giving birth.